Glyceraldehyde 3-Phosphate Dehydrogenase and Galectin from Dirofilaria immitis Excretory/Secretory Antigens Activate Proangiogenic Pathway in In Vitro Vascular Endothelial Cell Model - Manuel Collado-Cuadrado; Alfonso Balmori-de la Puente; Iván Rodríguez-Escolar; Elena Infante González-Mohino; Claudia Alarcón-Torrecillas; Miguel Pericacho; Rodrigo Morchón (Animals)
Heartworm disease is caused by Dirofilaria immitis, which mainly affects canids and felids. Adult D. immitis worms are located between the heart’s right ventricle and the pulmonary artery. These parasites produce an inflammatory and hypoxic process in the vascular endothelium. It has been demonstrated that D. immitis excretory/secretory antigens are able to stimulate the angiogenic process as a survival mechanism of D. immitis in the vascular endothelium, stimulating the proangiogenic pathway and related cellular processes. Our goal was to study the role of glyceraldehyde 3-phosphate dehydrogenase (GAPDH) and galectin (GAL) (proteins of D. immitis excretory/secretory antigens) plus vascular endothelial growth factor isoform A (VEGF-A) in the angiogenic process and their relationship with three cellular processes (cell proliferation, cell migration, and pseudocapillary formation) in an in vitro model of vascular endothelial cells. Cell viability and cytotoxicity were analyzed by live cell analysis and a commercial kit, respectively. VEGF-A, sVEGFR-2, VEGFR-1/sFlt, soluble endoglin, and membrane endoglin were analyzed by commercial ELISA kits. Cell proliferation, cell migration, and pseudocapillary formation were analyzed by MTT-based assay, the wound healing technique, and counting cell connections and cell clusters, respectively. rDiGAPDH+VEGF-A and rDiGAL+VEGF-A significantly increased the expression of sVEGFR-2, mEndoglin, and VEGF-A compared to cultures treated with only the proteins (rDiGAPDH and rDiGAL), VEGF-A, or unstimulated cultures. In addition, they also produced a significant increase in cell proliferation, cell migration, and pseudocapillary formation. Therefore, these proteins together with VEGF-A can activate the proangiogenic pathway and could be related to D. immitis survival in the circulatory system.